Karakteristik dan Persepsi Pengunjung untuk Pengembangan Wisata Edukasi di Taman Cadika Kota Medan - Sembiring, Elfiyanti; Badaruddin; Thoha, Achmad Siddik (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Cadika Park has long been a popular public space for outdoor learning and social activities. The development of Cadika Park into an educational tourism area needs to take into account the characteristics and perceptions of visitors. The purpose of this study was to analyse visitor perceptions for the development of educational tourism in Cadika Park. The research data came from drone mapping, field observations and interviews with questionnaires on field conditions and visitor characteristics and perceptions. Descriptive analysis was used to describe the field and questionnaire data to provide an overview of field conditions and visitor characteristics and perceptions. Analysis in the form of tables and graphs that quantitatively describe the distribution of characteristics and opinions of respondents in relation to the availability of objects and the potential for educational tourism development. The study found that almost all respondents perceived that Cadika Park has educational tourism objects. The Cadika Park area has natural potential for educational tourism in the form of flora, fauna and water. According to most respondents, forests and lakes are the most interesting objects that are widely used for educational activities.